1980
DOI: 10.1002/dev.420130406
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal influence of mild decompressions on hooded rats

Abstract: Frequent, brief, and mild prenatal decompressions caused decreases in newborn rats' viability and in survivors' "emotional" development. Both hypoxia and otic barotrauma contributed to these effects, but hypoxia, alone, did not affect offspring behavior in the open field or in a shock avoidance task.Prenatal exposure to high altitudes generally depresses birth weights and increases mortalities among the newborn (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For instance, within 7 days after birth, female rats appear to have higher catecholaminergic and serotonergic neurotransmitter activity compared to male rats [25,26]. Additionally, it was shown that neonatal asphyxia could induce long-lasting alterations in the serotonin metabolism of male but not in female rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, within 7 days after birth, female rats appear to have higher catecholaminergic and serotonergic neurotransmitter activity compared to male rats [25,26]. Additionally, it was shown that neonatal asphyxia could induce long-lasting alterations in the serotonin metabolism of male but not in female rats [27].…”
Section: Discussionmentioning
confidence: 99%